Molecular understanding of Indian untransfused thalassemia intermedia. (30th July 2015) - Nadkarni, A.; Dabke, P.; Colah, R.; Ghosh, K.
Summary: Background: The term thalassemia intermedia describe a form of thalassemia of intermediate severity, between the major transfusion‐dependent forms of the disease and the symptomless carrier states. The phenotypic diversity of β‐thalassemia results from its underlying genetic diversity. The wide clinical variability of these conditions leads to major difficulties in their management. The molecular basis of thalassemia intermedia is very heterogeneous. The clinical and hematological course of β‐thalassemia intermedia is influenced by a number of genetic factors. Methods and Results: The main aim of the study was to evaluate the effect of globin and nonglobin genetic modifiers on clinical severity of the disease. The study group consisted of 66 homozygous patients with β‐thalassemia [40 transfusion‐dependent thalassemia (TDT), 26 nontransfusion‐dependent thalassemia (NTDT)]. Hepatosplenomegaly was pronounced in the NTDT group. The presence of associated α‐thalassemia was significantly higher in untransfused patients ( P  <   0.05). The milder β‐thalassemia mutations, such as Cap site +1 (A→C), −88 (C→T), and −87 (C→G), were observed mainly in the NTDT group (9.61%) as against patients with TDT (1.25%). The cis‐DNA haplotypes, motifs, or polymorphisms around the gamma‐globin genes [(AT)x (T)y motif (38.4%), XmnI (76.92%)and the Aγ‐δ intergenic region haplotype T (73.07%) and Pre Gγ globin gene haplotype TAG (46.15%)] contributed significantly in amelioration of the disease severity. Conclusion: Our study emphasizes the complexity of genetic interactions that underlie the phenotype of β‐thalassemia and highlights the importance of epistatic factors and the regulation of HbF production in β‐thalassemia syndromes.